Emotional Dynamics: Grieving Experiences of Women After Abortion - Ekklesia, Petra; Salsabila, Raina; Putri, Sofia Tri (Universitas PGRI Yogyakarta, 2026)
This study explores the complex emotional dynamics and grieving process experienced by a woman following an induced abortion, utilizing Kübler-Ross’s five-stage grief model (denial, anger, bargaining, depression, acceptance) as a theoretical framework. A qualitative narrative approach was employed, with data collected through an in-depth, semi-structured online interview with a 20-year-old participant who underwent an abortion at age 18. Non-participant observation of non-verbal cues supplemented the interview data. Thematic analysis was conducted to map the subject’s experiences onto the stages of grief. Findings confirm that the participant navigated all five stages of grief, though in a non-linear and highly individual sequence. The depression stage was notably prolonged, while the eventual movement toward acceptance was significantly facilitated by entering a new, supportive romantic relationship, which provided a crucial